Clinical teaching strategies in nursing - Gaberson, Kathleen B.; Oermann, Marilyn H.; Shellenbarger, Teresa (Springer Publishing Company, LLC, 2015)
The fourth edition of this text provides a comprehensive framework for planning, guiding, and evaluating learning activities for graduate and undergraduate nursing students in numerous clinical settings. A resource for clinical faculty, it addresses the distinct requirements of clinical learning as opposed to classroom learning and provides proven strategies to maximize clinical education. The revision features expanded content on teaching graduate students, regulatory issues affecting distance education, and the use of social media. It covers establishing and using dedicated education units (DEUs), the challenges of student access to electronic health records and documentation of care, and reducing the demands of clinical staff members when multiple students rotate through a praticular setting.